Geliat Usha Mikro Ibu-bu Rumah Tangga dari Keluarga Miskin, Pembuatan Abon Bandeng dan Kecap di Gunung Anyar Kota Surabaya - Al-Amin, Mukayat; Maroâ€™ah, Siti (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
The problems and obstacles faced by Abon Bandeng business group "Barokah" and Kecap "Kurma" are: 1. The making process is still using traditional tools and in very little capacity, so that the products are produced less than the maximum and in small capacity. So when there is a rather large order they can not afford to fill the order in due to lack of equipment that is not adequate for more production capacity. 2. Marketing management that still rely on orders and exhibitions of food products, this results in less sustainable production, rather than resulting in profits that can not be maximal / uncertain. Therefore, based on the need for solutive and strategic steps to overcome the problem of business groups to be more productive and highly competitive, these steps antaralain: 1. The need to modernize the equipment so as to produce products that berkuwalitas and competitive can do more production. 2. The need to improve the quality of group resources in terms of marketing of production, this quality improvement can be done by doing marketing training / marketing ofÂ production. So that the already sustainable production can be marketed optimally. This devotion aims to 1) This Business Group can produce maximally both in terms of production capacity and in terms of high quality of competitive production. 2) Increasing the quality of human resources of the group members in terms of marketing of the products so that the production can be sold / marketed maximally. The method used in this service is the approach done by using FGD (Focus Group Discussion) method combined with participatory research method that is by studying, finding and rediscovering business problem that happened in the Development of Mother House Business Group Date.